Solute-Solvent Energy Transfer And Cooling Kinetics of Photoexcited S1Trans-Stilbene Probed With Picosecond Raman Spectroscopy: Comparison Between Chloroform and Chloroform-d Solutions. Issue 1 (1999) - Iwata, Koichi; Hamaguchi, Hiro-o
Abstract : Cooling kinetics of trans -stilbene ( t SB) photoexcited to a vibrationally excited state in the first excited singlet (S1 ) manifold was studied with picosecond time-resolved Raman spectroscopy. The observed cooling curves of S1 t SB in chloroform (CHCI3 ) and in chloroform-d (CDCl3 ) were identical within the experimental uncertainties. For S1 t SB in chloroform, there was no experimental evidence for strong intermolecular vibration-vibration (V–V) resonance energy transfer in the picosecond to sub-picosecond time region.